INOVASI MODEL BISNIS DAN INOVASI KONSEP BISNIS SEBAGAI KONSEP INOVASI INKREMENTAL DAN RADIKAL (STUDI KASUS PADA HOTEL DAN HOMESTAY DI BANYUWANGI) - Rifka Arinda Noviasari; Sari Narulita (Nusantara Hasana Journal, 2023)
This research aims to look at business capital and business innovation concepts implemented in hotels in Banyuwangi. Banyuwangi was chosen because of its status as a city with a growing tourism industry which has experienced rapid growth in the last 10 years. A total of 124 hotel and homestay samples contributed to this research. The research method used was purposive sampling with several criteria. The research results show that first, the concept of innovation and business model innovation in the tourism sector, especially hotels, really needs new ideas to develop it. Exploitation of business models or business innovation will have an impact when implemented, especially for hotels in tourist destination areas. Second, the innovation carried out can be technological or non-technological depending on the aim of increasing competitiveness. This research suggests that for further research it would be better to carry out a qualitative approach to get more comprehensive results.